A Case of Impetigo Cured with Homoeopathic Similimum (Advancements in Homeopathic Research, 2022)
Background Impetigo is a highly contagious infection of the epidermis, seen especially among children, and transmitted through direct contact. Over 140 million people are suffering from impetigo at each time point and approximately 100 million are children. It is type of bacterial diseases which is highly contagious and spread from close contacts. Most common bacteria are staphylococcus aureus and Group A streptococcus. Impetigo exits in two forms of, namely impetigo contagiosa which is also known as the non-bullous form and the second one being bullous impetigo which presents with large and fragile bullae. Method This article is about a female child three years of age suffered from impetigo contagiosa and responded well to homoeopathic medicine. Result Homoeopathic medicine, Hepar sulphuricum in 200 potency, was prescribed on the basis of totality of symptom, and child completely cured within two weeks of homoeopathic treatment. Interpretation Modern system or allopathic system of medicines uses antibiotics and topical corticosteroids for these problems which may have some side effects. Homoeopathic medicines are safer for children because it has no side effects if selected on the basis of Homoeopathic principles. Conclusion In certain skin disorders like Impetigo contagiosum homoeopathy medicines can be used as alternate mode of treatment.
Keywords: Impetigo; Homoeopathy; Staphylococcus; Streptococcus